Modelling the Coupled and Coordinated Development between China’s Cross-border E-commerce Supply Chain and Economic System - Xinxin Li; Chunfang Zheng; Tongtong Wang (Discrete Dynamics in Nature and Society)
This study constructs a coupling model and establishes an index system for the coupled and coordinate development between cross-border e-commerce supply chain system and economic system. The index system adopts supply chain, foreign trade, e-commerce, e-commerce logistics, economic development, social consumption, talent environment, and technological innovation as sequential covariates. The calculation shows that the first three batches of 35 cross-border e-commerce comprehensive pilot areas (CBECCPA in brief) in China, in 2017, are classified into three degrees of the coupled and coordinated development: superior, good, and moderate. The study provides useful recommendations for promoting cross-border e-commerce supply chain, such as to pursue high-quality balanced development, to cultivate professional composite talents, to encourage innovation and entrepreneurship, and to create a favorable economic environment.